The Turkish and Moroccan Second Generation and their Comparison Group Peers in Amsterdam and Rotterdam : Technical Report and Codebook : TIES 2006-2007 - The Netherlands. - Hornstra, N. E. (DANS Publications., 2012)
This important study offers detailed information obtained by interviewing 1505 Dutch respondents, all second-generation Turkish or Moroccan, alongside members of a native Dutch comparison group. The respondents, all aged 18-35 and residing in Amsterdam or Rotterdam, supplied information relating to their cultural, social and economic integration in the Netherlands. The book describes the strategies deployed to select and interview respondents, including an account of problems and adopted solutions. Furthermore, it outlines the sampling frame and sample selection, as well as issues of non-respo.